2021
DOI: 10.1186/s12981-021-00422-3
|View full text |Cite
|
Sign up to set email alerts
|

Trends and correlates of HIV prevalence among adolescents in South Africa: evidence from the 2008, 2012 and 2017 South African National HIV Prevalence, Incidence and Behaviour surveys

Abstract: Background Adolescents are at increased risk of HIV infection compared to other age groups. There is an urgent need for strategic information that will inform programmes to reduce risk and vulnerability to HIV and reverse the pattern of increasing HIV infection as they transition to adulthood. This paper analysed trends and factors associated with HIV prevalence among adolescents in South Africa using the national HIV population-based household surveys conducted in 2008, 2012 and 2017. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 19 publications
4
20
0
Order By: Relevance
“…This is consistent with the literature that suggests that adolescents in South Africa are highly susceptible to HIV (see Fig. 3) (3,13,14). This risk of HIV was highest between 15 and 36 years old.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with the literature that suggests that adolescents in South Africa are highly susceptible to HIV (see Fig. 3) (3,13,14). This risk of HIV was highest between 15 and 36 years old.…”
Section: Discussionsupporting
confidence: 93%
“…South Africa has approximately 360,000 adolescents ages 10 to 19 living with HIV, over a third of all adolescents living with HIV (ALHIV) in sub-Saharan Africa (SSA) [ 1 – 3 ]. KwaZulu-Natal province has the highest number of ALHIV in South Africa [ 3 5 ]. An estimated one in five adolescents living with HIV across the world was perinatally infected, and 79% of adolescents with perinatally-acquired HIV (APHIV) reside in SSA [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…An estimated one in five adolescents living with HIV across the world was perinatally infected, and 79% of adolescents with perinatally-acquired HIV (APHIV) reside in SSA [ 6 ]. Health policy has largely overlooked social health inequities among APHIV [ 5 ], who face unique risks related to their sexual and reproductive health (SRH) [ 7 ]. A 2021 scoping review identified gaps for APHIV pertaining to knowledge of SRH and access to SRH services, high rates of risky sexual practices, and low family planning uptake [ 8 ], leading to higher rates of unintended pregnancy than their HIV-negative counterparts [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescents aged 10-19 years 28 have unique challenges and are at increased risk of HIV infection compared to other groups. 29 Therefore, exploring their perspectives on how DSD models influence the utilization of services is critical. Their insights can help improve the availability and quality of HIV prevention and treatment programs for adolescents.…”
Section: Introductionmentioning
confidence: 99%